2014
DOI: 10.1523/jneurosci.1195-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-β-Induced Action Potential Desynchronization and Degradation of Hippocampal Gamma Oscillations Is Prevented by Interference with Peptide Conformation Change and Aggregation

Abstract: The amyloid-␤ hypothesis of Alzheimer's Disease (AD) focuses on accumulation of amyloid-␤ peptide (A␤) as the main culprit for the myriad physiological changes seen during development and progression of AD including desynchronization of neuronal action potentials, consequent development of aberrant brain rhythms relevant for cognition, and final emergence of cognitive deficits.The aim of this study was to elucidate the cellular and synaptic mechanisms underlying the A␤-induced degradation of gamma oscillations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

29
122
5
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(160 citation statements)
references
References 47 publications
29
122
5
4
Order By: Relevance
“…A similar mechanism has previously been shown to underlie the A␤-induced decrease of glutamatergic synaptic transmission (Hsieh et al, 2006). Of note, no p4-related upregulation of IPSCs was seen in the present study, as originally reported by Kittler et al (2000). However, the absence of a p4-induced increase of GABA receptors is in line with previous data from cortical pyramidal neurons (Kurotani et al, 2008), indicating that this phenomenon may be cell-type specific.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…A similar mechanism has previously been shown to underlie the A␤-induced decrease of glutamatergic synaptic transmission (Hsieh et al, 2006). Of note, no p4-related upregulation of IPSCs was seen in the present study, as originally reported by Kittler et al (2000). However, the absence of a p4-induced increase of GABA receptors is in line with previous data from cortical pyramidal neurons (Kurotani et al, 2008), indicating that this phenomenon may be cell-type specific.…”
Section: Discussionsupporting
confidence: 93%
“…The prevention of the A␤-induced decline of IPSCs by p4, a peptide that inhibits the dynaminmediated removal of GABA A receptors from the plasma membrane (Kittler et al, 2000), indicates that A␤ exerts its effect via receptor endocytosis. A similar mechanism has previously been shown to underlie the A␤-induced decrease of glutamatergic synaptic transmission (Hsieh et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the amyloid ␤-peptide (A␤) 4 associated with Alzheimer disease, many studies indicate that pre-fibrillar intermediates present during the aggregation trigger neuronal dysfunction, rather than the fibrils per se (14). However, mature fibrils can also exert more potent toxic effects than pre-fibrillar forms of A␤ in certain experimental systems (15).…”
mentioning
confidence: 99%